Neoadjuvant Therapy for Resectable Pancreatic Cancer: An Evolving Paradigm Shift - Chawla, Akhil; Ferrone, Cristina R. (Frontiers in Oncology, 2019)
Non-metastatic pancreatic adenocarcinoma (PDAC) is associated with a high rate of recurrence and lethality. In addition, less than half of all patients are able to complete systemic therapy after curative-intent pancreatectomy. With its well-known potential benefits, this report highlights the current prospective data relevant to the use of neoadjuvant systemic therapy in resectable PDAC. Recently, there have been numerous reports, many of which consist of long-awaited multi-intuitional trial data evaluating the use of neoadjuvant systemic chemotherapy in non-metastatic PDAC as well as the use of combination chemotherapy regimens in the adjuvant setting. Currently, recommended guidelines for neoadjuvant systemic therapy only exist for borderline-resectable and locally-advanced disease. Given the plethora of new data, there has been a shift in the paradigm of how resectable pancreatic cancer is treated at certain centers across the world. This review highlights the relevant available data from recent sentinel prospective trials and how they relate to the systemic treatment of resectable PDAC in the neoadjuvant setting.